2003
DOI: 10.1007/s00442-002-1134-y
|View full text |Cite
|
Sign up to set email alerts
|

Helpful habitant or pernicious passenger: interactions between an infaunal bivalve, an epifaunal hydroid and three potential predators

Abstract: The importance of positive interspecific interactions within physically stressful habitats has received increased attention from community ecologists. The exposed sandy beach is an example of a physically rigorous environment where biological interactions have long been considered insignificant. We examined the interaction between the infaunal clam, Donax variabilis, and the hydroid, Lovenella gracilis, on exposed sandy beaches in North Carolina. Epibiotic occupation of Donax by hydroids has been repeatedly ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Wilber et al (2003) similarly demonstrated avoidance of turbidity generated from beach nourishment by the visually orienting bluefish and attraction to turbid fill sites by the northern kingfish in New Jersey. Avoidance of turbidity makes sense for visually orienting predatory fishes such as pompano (Manning & Lindquist 2003, Manning et al 2013) and diving seabirds such as terns (Cyrus & Blaber 1987). In contrast, flounders are ambush predators, which, due to their camouflage by sand, do not need to be able to see farther than a few centimeters in order to capture more closely approaching prey.…”
Section: Implications For Predators Of Benthic Invertebratesmentioning
confidence: 99%
“…Wilber et al (2003) similarly demonstrated avoidance of turbidity generated from beach nourishment by the visually orienting bluefish and attraction to turbid fill sites by the northern kingfish in New Jersey. Avoidance of turbidity makes sense for visually orienting predatory fishes such as pompano (Manning & Lindquist 2003, Manning et al 2013) and diving seabirds such as terns (Cyrus & Blaber 1987). In contrast, flounders are ambush predators, which, due to their camouflage by sand, do not need to be able to see farther than a few centimeters in order to capture more closely approaching prey.…”
Section: Implications For Predators Of Benthic Invertebratesmentioning
confidence: 99%
“…Manning & Lindquist (2003) demonstrated a positive interaction where the clam Donax variabilis facilitated epibiotic occupation by providing a stable substrate for attachment of the hydroid Lovenella gracilis; the hydroid defended the clam against fishes by means of its nematocysts, but facilitated predation by crabs, because projection of the hydroid above the surface of the sand allowed the crabs to more readily detect clams. Depending on relative predation pressure, the occupation of D. variabilis by L. gracilis was characterized as beneficial or detrimental to the host.…”
Section: Predation Mutualism and Parasitismmentioning
confidence: 99%
“…Predators perform synchronized migrations that follow daily or seasonal changes in zonation of prey (Ansell et al 1999). Selective predation by fish and aerial predators, depending on beach levels, could also affect zonation patterns differentially, depending on individual sizes and prey availability (Takahashi et al 1999, Manning & Lindquist 2003, Yu et al 2003. Active microhabitat selection could occur in order to avoid predators or search for food concentrations (Takahashi & Kawaguchi 1998).…”
Section: Spatial Structure and Patch Dynamicsmentioning
confidence: 99%
“…Surprisingly, however, there are circumstances where biofouling is beneficial, or at least, does not affect production. For example, fouling can enhance shellfish growth (Dalby and Young 1993), increase primary production of phytoplankton and therefore food availability to shellfish (Lodeiros et al 2002;Ross et al 2002;Le Blanc et al 2003), provide shellfish with protection against predation (Wahl et al 1997;Manning and Lindquist 2003), facilitate the settlement of commercially farmed shellfish (Hickman and Sause 1984;Fitridge 2011) or mitigate disease risk (Paclibare et al 1994). These examples, however, are the exception, and biofouling is primarily deleterious to the cost effective production of shellfish and fish.…”
Section: Common Fouling Organisms In Aquaculture Settingsmentioning
confidence: 99%